Sosialisasi Konsep 4P (Pray, Prediction, Preventif, dan Protection) Kepada Pelatih dan Calon Pelatih Cabang Olahraga Beladiri - Alif, Muhammad Nur; Tatang Muhtar; Sagitarius, Sagitarius (LPPM Universitas HKBP Nommensen, 2024)
The 4P concept is a new idea in the field of martial arts activities. This concept was born out of concern about cases of violence that occur among the community, especially women and children. The 4P concept must be understood by teachers, martial arts trainers and martial arts practitioners so that the public understands more about the importance of understanding the concept of self-defense as a whole and in general. Socialization activities for the 4P concept were carried out in several locations in two different cities. The main target of this activity is martial arts practitioners who teach martial arts activities directly. Activities are carried out in several locations with a time allocation of one day for each session. The total number of participants who took part in this socialization activity was 120 people, consisting of self-defense trainers and self-defense practitioners, divided into 3 different times. Kata Kunci: Socialization, Trainer, Martial Arts